Adsorption of Copper (II) from Aqueous Solution by Using Carbonized Peanut Hull: Determination of the Equilibrium, Kinetic and Thermodynamic Parameters - Senel, Gulsad Uslu (My University, 2020)
In this study, the effect of temperature, pH, initial metal concentration and adsorbentdosage on Cu(II) adsorption onto carbonized peanut hull (PHC) was investigated. Activatedcarbon was prepared from peanut hull. It was produced by carbonization in carbon dioxideatmosphere at 500°C for 1.0 h. The maximum Cu (II) adsorption capacity was obtained as 168.16mg/g for 500 mg/L initial Cu (II) at pH = 4.0 and 60 °C. The Freundlich and Langmuir adsorptionmodels were used for the mathematical description of the adsorption equilibrium. The bestinterpretation for the experimental data was given by the Freundlich isotherm and the maximumadsorption capacity was obtained. Batch adsorption models, based on the assumption of thepseudo-first and pseudo-second order mechanism, were applied to examine the kinetics of theadsorption. Kinetic data fitted the pseudo-second kinetic order model. Thermodynamic functions,the change of free energy (?Go), enthalpy (?Ho) and entropy (?So) of copper adsorption on PHCwere calculated as -23.21 kjmol-1(at 60oC), 15.94 kjmol-1and 117.59 kjmol-1 K-1, respectively,indicating the spontaneous, endothermic and the increased randomness nature of Cu2+ adsorption.The results show that adsorption of Cu (II) on PHC is an.
Keywords: Kimya; Uygulamalı; Çevre Bilimleri